Distance to sports facilities and low frequency of exercise and obesity: a cross-sectional study - Auriba Raza; Anna Pulakka; Linda L Magnusson Hanson; Hugo Westerlund; Jaana I. Halonen (BMC, 2022)
Abstract Background Little research has investigated the associations between proximity to physical activity facilities and behavior-related health and the majority have focused on proximity from home address. We add to the literature by examining proximity of these facilities to work and home address and including a wide range of physical activity facilities. We assess the associations for proximity of physical activity facilities from home and work address with self-reported frequency of exercise and obesity. Methods Our analytical sample of 7358 participants was from the 2018 wave of the Swedish Longitudinal Occupational Survey of Health. We used logistic binomial regression adjusting for age, sex, education, civil status, individual socioeconomic status, neighborhood socioeconomic status, number of children under 12 years of age, work strain, and chronic disease. Results Longer distance from home to paid outdoor and paid indoor physical activity facilities was associated with low frequency of exercise (fully adjusted Relative Risk for both 1.01, 95% CI 1.01-1.02). Associations of any or free outdoor facility with low frequency of exercise were not robust. Findings also indicated associations between long distance from workplace to any and paid outdoor facility and low frequency of exercise. Results for obesity were in the similar direction, however, these were not statistically significant. Conclusion Increased distance of paid outdoor and paid indoor physical activity facilities from home and of paid outdoor facilities from work was associated with low frequency of exercise. Longitudinal and larger studies are needed to confirm our findings, particularly regarding obesity.